2007
DOI: 10.1111/j.1741-3737.2007.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Time Use: Labor Divisions and Schooling in Indonesia

Abstract: Data from the Worker and Iron Status Evaluation are used to examine gendered patterns in children’s time in market and nonmarket work, schooling, and leisure in Indonesia (N= 2,929). Boys spend more time in market work; girls spend more time in nonmarket work. Work responsibilities increase with age as well as gender differentials in children’s time use. By age 18, girls spend nearly 1 more hour per day working and enjoy significantly less leisure time, but the gender gap in schooling is not significant, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…Though the ratio of male to female migrants in the region is relatively equal, migration dynamics may differ (Global Migration Group 2014). Families may limit prolonged education investments in girls if the labor market is less hospitable to women (Buchmann 2000), and girls' more intensive household labor contributions may tie them to the home, particularly if younger sisters are not available to replace them in their domestic responsibilities (Herrera and Sahn 2013;Hsin 2007). However, labor opportunities for women and girls are increasingly available, which may encourage labor migration, and the same factors that discourage parents from allowing their daughters to migrate may encourage urban households to receive girls, especially those who contribute domestic service (Moya 2007).…”
Section: Youth Migration: a Family-based Strategymentioning
confidence: 99%
“…Though the ratio of male to female migrants in the region is relatively equal, migration dynamics may differ (Global Migration Group 2014). Families may limit prolonged education investments in girls if the labor market is less hospitable to women (Buchmann 2000), and girls' more intensive household labor contributions may tie them to the home, particularly if younger sisters are not available to replace them in their domestic responsibilities (Herrera and Sahn 2013;Hsin 2007). However, labor opportunities for women and girls are increasingly available, which may encourage labor migration, and the same factors that discourage parents from allowing their daughters to migrate may encourage urban households to receive girls, especially those who contribute domestic service (Moya 2007).…”
Section: Youth Migration: a Family-based Strategymentioning
confidence: 99%
“…Keberadaan pekerja anak akan menimbulkan hambatan dalam pembangunan sumber daya manusia (Becker, 1962(Becker, , 1965Hsin, 2007;Handono, 2009). Anak yang bekerja akan kehilangan haknya dalam mendapatkan pendidikan optimal yang dapat merugikan masa depannya dan berpotensi mengalami gangguan kesehatan di masa yang akan datang (Beegle, Dehejia and Gatti, 2009), serta rentan mengalami masalah psikologi dan sosial (Beegle et al, 2008;Wolff, 2008;Beegle, Dehejia and Gatti, 2009;Emerson and Souza, 2011 (Gibbons, Huebler and Loaiza, 2005 Pekerja anak disebabkan oleh dua faktor, yaitu faktor penarik dan pendorong.…”
Section: Pekerja Anak DIunclassified
“…Yet the evidence on rural-urban differences of children's care and domestic work varies by country. Hsin (2007), exploiting a longitudinal survey administered in a rural district east of Yogyakarta in Indonesia, investigated gender differences in children's time use, and found that among children aged eight to 18, boys spend more time in market work, while girls spend more time in care and domestic work. Work responsibilities also increase with age: by age 18, girls spent on average almost one hour more per day working than boys when market and care and domestic work were combined (Hsin, 2007).…”
Section: Household Level Determinants Of Care and Domestic Workmentioning
confidence: 99%
“…Hsin (2007), exploiting a longitudinal survey administered in a rural district east of Yogyakarta in Indonesia, investigated gender differences in children's time use, and found that among children aged eight to 18, boys spend more time in market work, while girls spend more time in care and domestic work. Work responsibilities also increase with age: by age 18, girls spent on average almost one hour more per day working than boys when market and care and domestic work were combined (Hsin, 2007). By contrast, in the Bangladeshi context the differences between urban and rural children are small, as urban girls spend on average only four percent less of their time on housework compared to rural female peers (Rabbani, 2006).…”
Section: Household Level Determinants Of Care and Domestic Workmentioning
confidence: 99%